Epidemiology of pediatric sarcoma in Iran. Issue 1 (27th June 2022) - Azizmohammad Looha, Mehdi; Akbari, Atieh; Akbari, Mohammad Esmaeil; Zarean, Elaheh; Mehrvar, Narjes; Khodakarim, Soheila
Abstract: Background: Pediatric sarcomas are divided into two major groups of soft‐tissue sarcomas (STSs) and malignant bone tumors (MBTs). Aims: The aim of the present study was to determine the incidence and survival rate of STSs and MBTs in the Iranian population based on diagnosis date, gender, age, and histological types. Methods and Results: Data was retrieved from Iran National Cancer Registry between 2008 and 2015. The dataset was classified according to the third edition of the International Classification of Childhood Cancer. The survival information was merely available for 291 (21% of total data), including 142 (49%) MBTs and 149 (51%) STSs. The age‐standardized incidence rates (ASIRs) and five‐year survival rates were calculated. Conclusion: The present study is the first comprehensive study of pediatric sarcomas in Iran, in which a lower incidence and survival rate of MBTs and STSs compared with high‐income countries were found. However, the survival rates of these malignancies were higher in high‐income countries compared to Iran. This study showed the need to improve the quantity and quality of the population‐based registry in Iran for acquiring progress in the prevention and control of sarcomas.